Origin of Current‐Controlled Negative Differential Resistance Modes and the Emergence of Composite Characteristics with High Complexity. (28th August 2019) - Li, Shuai; Liu, Xinjun; Nandi, Sanjoy Kumar; Nath, Shimul Kanti; Elliman, Robert Glen
Abstract: Current‐controlled negative differential resistance has significant potential as a fundamental building block in brain‐inspired neuromorphic computing. However, achieving the desired negative differential resistance characteristics, which is crucial for practical implementation, remains challenging due to a lack of consensus on the underlying mechanism and design criteria. Here, a material‐independent model of current‐controlled negative differential resistance is reported to explain a broad range of characteristics, including the origin of the discontinuous snap‐back response observed in many transition metal oxides. This is achieved by explicitly accounting for a non‐uniform current distribution in the oxide film and its impact on the effective circuit of the device rather than a material‐specific phase transition. The predictions of the model are then compared with experimental observations to show that the continuous S‐type and discontinuous snap‐back characteristics serve as fundamental building blocks for composite behavior with higher complexity. Finally, the potential of our approach is demonstrated for predicting and engineering unconventional compound behavior with novel functionality for emerging electronic and neuromorphic computing applications. Abstract : A material‐independent model of current controlled negative differential resistance (NDR) is developed to explain continuous S‐type and abrupt snap‐back NDR characteristics and to show that these serve as fundamental building blocks for compound NDR behavior with higher complexity and potential novel functionalities.